Beckwith-Wiedemann Syndrome and Dental Features: a Case Report - Longo, Bruna Cristina; Turcatto, Rafael Chimiloski; Rangel, Ana Lúcia Carrinho Ayroza; Amorin, Elaine Manoela Porto; Davidoff, Denise Cesar de Oliveira; Hoshi, Adriano Tomio; Tomasin, Maria de Fátima; Hirata, Francielle Carneiro; Souza, Maria Daniela Basso de (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Beckwith-Wiedemann Syndrome (BWS) is characterized by a disorder on chromosome 11p15, whose loci have growth-regulating genes. Among the numerous clinical features such anterior abdominal wall defects, omphalocele and genital abnormalities, the most prevalent is macroglossia, which can lead to disturbances in craniofacial growth. This report brings a case of a 9-year-old male child with the syndrome treated at the School of Dentistry, State University of Western Paraná, Brazil. It was suggested that observed dental abnormalities, along with the commonly features described in the literature, may be a part of the broad spectrum of the syndrome.